STRATEGI PEMERINTAH KOTA MALANG DALAM MENINGKATKAN PENERIMAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (Studi pada Dinas Pendapatan Daerah Kota Malang) - PRASETYO, DIMAS NOER ARI (Jurnal Mahasiswa Perpajakan, 2015)
This research is descriptive research with qualitative approach. Data source that used is primary data and secondary data. Primary data is in the form of observation and interview result, while secondary data is in the form of documents of Renstra, Lakip, Renja, and profile book of Dinas Pendapatan Daerah. Data analysis on this research is interactive data analysis model of Miles and Huberman. Strategy undertaken by Dinas Pendapatan Daerah include intensification and extensification strategy. On implement that strategy, Dinas Pendapatan Daerah Kota Malang face some problems, including less obediently Wajib Pajak, less strong foundation law, and there’s desire from Wajib Pajak to do fraud. Keywords : Intensification strategy, extensification strategy